Revision Total Hip Arthroplasty in the Setting of a Well-Fixed Cup: Early Report on the Cup-in-Cup Technique - Stambough, Jeffrey B.; Nam, Denis; Haynes, Jacob A.; Sassoon, Adam A.; Bohnenkamp, Frank C.; Barrack, Robert L.; Nunley, Ryan M. (The Journal of Hip Surgery, 2017)
When faced with a well-fixed acetabular component during revision total hip arthroplasty (THA) in the setting of recurrent instability, reconstructive options are limited, and consequences can prove dire if removal leads to severe bone loss or pelvic discontinuity. Our aims are to report the surgical technique, early survivorship, radiographic improvements, and complications on a consecutive, retrospective series of 13 hips in 12 patients who were treated with a cup-in-cup surgical technique to address multiply recurrent dislocations in the setting of a well-fixed cup. If determined to be stable and acceptably positioned upon intraoperative assessment, the acetabular component is retained, a second shell is cemented into the preexisting cup, and a dual mobility or standard polyethylene liner bearing is utilized. At 2-year minimum follow-up, the cup-in-cup arthroplasty exhibited an overall 85% survivorship. Two subjects required subsequent revisions: one for infection and one for ongoing instability in the setting of general noncompliance. No revisions were performed for loosening of the cup-in-cup interface. The median affected leg length was increased by 2.8 mm (p = 0.04) and horizontal offset improved by an average of 6.9 mm (p < 0.001). There were a total of four dislocations in two subjects after cup-in-cup revision arthroplasty with no failures at the cup–cup cement interface. Our series demonstrates acceptable early outcomes in terms of improved stability and decreasing the need for further revision surgery while utilizing the cup-in-cup revision arthroplasty technique in situations of recurrent dislocations.
Keywords: revision hip arthroplasty; recurrent instability; cup-in-cup technique; well-fixed acetabular cup